O ritual mapimaí no processo de construção da territorialidade paiter suruí - Adnilson de Almeida Silva; Carlandio Alves da Silva; Sheila Castro dos Santos; Adriana Francisca de Medeiros; Almir Narayamoga Suruí (Confins)
The article seeks to present how the universe of the Paiter Suruí is conceived and organized by this ethnic group. The construction follows the visions and experiences of action and space of this group inhabiting the States of Mato Grosso and Rondônia. During the Mapimaí ritual– “the creation of the world” – they meet in phenomena and symbolic representations their identities, so that in the event the spirituality, of which the territoriality is integral, part, becomes more noticeable and therefore materialized. The design of this study is based in empirical experience (Mapimaí) and theoretical frameworks that discuss the indigenous question. It is noteworthy that the ritual, as representation and cultural event, has been "dormant" for several years due to factors external to ethnicity. It has been reactivated due to the understanding by Paiter Suruí thet it strengthens their identity as a people and provides spiritual and affective ties strengthening, which allows ensuring the territoriality, considering the constant threats to Indigenous Land Paiterey Garah (Sete de Setembro)